Darth Vader and son - Brown, Jeffrey, 1975- (San Francisco : Chronicle Books, 2012)
A collection of humorous one-panel strips that imagine Darth Vader dealing with a four-year-old Luke Skywalker as a parent.
"Lucas Books"--Cover p. [4].
Publisher's Weekly, April 2012.
Publisher's Weekly.
Adult
Keywords: Vader, Darth (Fictitious character) -- Comic books, strips, etc. -- Fiction; Skywalker, Luke (Fictitious character) -- Comic books, strips, etc. -- Fiction; Fathers and sons -- Comic books, strips, etc. -- Fiction; American wit and humor, Pictorial; Vader, Darth (Fictional character) -- Comic books, strips, etc. -- Fiction; Skywalker, Luke (Fictional character) -- Comic books, strips, etc. -- Fiction; Father-son relationship -- Comic books, strips, etc. -- Fiction; Wit and humor; Star Wars fiction; Comic books, strips, etc; Comic books, strips, etc; Star Wars fiction; Star Wars fiction; Comic books, strips, etc